THE CITY UTILIZATION MANAGEMENT CASE STUDY OF LAND USE DYNAMICS AND ECONOMIC GROWTH IN BANDAR LAMPUNG CITY - Bambang Utoyo S. (Universitas Sebelas Maret, 2015)
In the future, the urban area will be the area that gets more complex, covered by a variety of social, economic and environment arising from population growth in the region and in line with the dynamics of globalization, democratization and decentralization. The purposes of this study is to describe and analyze the dynamics of land use and growth in the area for 1 (one) a decade in Bandar Lampung. This research is a descriptive study using documentation for secondary data obtained from the BPS at two (2) different time points (t0 and t1). The analysis model used to assess the focus of research using quantitative analysis Location Quotient (LQ) and Shift-Share Analysis (SSA). The results showed that: (1) During a decade in Bandar Lampung has occurred the utilization land for industrial use; settlements and services were increasingly widespread. While the use of land that is not cultivated; swamps and forests tend to be diminishing at a rate; patterns and impact varied in each parts of the city; (2) For almost a decade of economic growth in Bandar Lampung supported by sectors of the economy outside agriculture and mining and quarrying. While in the long term competitiveness of economic growth in the city was supported by the agricultural sector; Non-oil processing industry; and finance, leasing and services company. And the third (3) factors of economic growth, population growth and government policy in the form of spatial planning as well as the entry into force of the market mechanism was a trigger factor that reflected changes in land use in urban areas. The suggestions and recommendations as well as follow up on the policy implications that can be done in Bandar Lampung, including : changing the necessary incentives and dis-incentives policy in controlling land utilization, giving the opportunity cost that owned land resources, both economic and non -economic. Additionally, in efforts to achieve sustainable urban development, expansion of public access required in determining the allocation of land use and the provision of public space is increasingly widespread and qualified as a form of services provided by the municipality to citizens.